2008
DOI: 10.1016/j.physa.2007.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal properties of Pyrex and silicon surfaces blasted with sharp particles

Abstract: The blasting of brittle materials with sharp particles is an important fabrication technology in many industrial processes. In particular, for microsystems, it allows the production of devices with feature sizes down to few tens of microns. An important parameter of this process is the surface roughness of post-blasted surfaces. In this work the scaling properties of Pyrex glass and silicon surfaces after bombardment with alumina particles are investigated. The targets were bombarded at normal incidence using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The width of the f (α) spectrum = α max − α min can be used to indicate the complexity of a structure: Monofractal structures give narrow spectra, whereas multifractal distributions give broader spectra [34,35]. The degree of multifractality of the structures in MR fluids for different (a) particle concentrations and different (b) frequencies is shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…The width of the f (α) spectrum = α max − α min can be used to indicate the complexity of a structure: Monofractal structures give narrow spectra, whereas multifractal distributions give broader spectra [34,35]. The degree of multifractality of the structures in MR fluids for different (a) particle concentrations and different (b) frequencies is shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…The observed multifractal behaviour can be partly interpreted in terms of the spatial intermittency [54,55] and the origin of the multifractal hidden in the fracture surface may be the long range correlations of the intermittent fluctuation [41,56]. A basic foaming process can be divided into three steps [4]: (1) temperature increase or a pressure decrease; (3) cell growth and coalescence, a combination of mass transfer and fluid dynamics.…”
Section: The Dependence Of ∆F With Respect To the Pp/pe Ratiomentioning
confidence: 99%
“…Raoufi et al analyzed the multifractal spectrum of ITO thin films prepared by electron beam deposition method and the f (α) shapes of ITO thin films remained left hooked after annealing at 200 • C and 300 • C [40]. Moktadir et al researched the multifractal properties of Pyrex and silicon surfaces blasted with sharp particles, and found that the long-range correlations were the origin of the multifractal behaviour [41].…”
Section: Introductionmentioning
confidence: 99%